2007
DOI: 10.1364/ao.47.000a32
|View full text |Cite
|
Sign up to set email alerts
|

Holographic generation of complex fields with spatial light modulators: application to quantum key distribution

Abstract: There has been considerable interest recently in the generation of azimuthal phase functions associated with photon orbital angular momentum (OAM) for high-dimensional quantum key distribution. The generation of secure quantum keys requires not only this pure phase basis but also additional bases comprised of orthonormal superposition states formed from the pure states. These bases are also known as mutually unbiased bases (MUBs) and include quantum states whose wave functions are modulated in both phase and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
63
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 21 publications
(20 reference statements)
0
63
0
Order By: Relevance
“…The superior security advantages of OAM channels have also been demonstrated in both classical and quantum communication systems. [14][15][16][17][18][19] OAM-based optical communications can be classified into two different categories: OAM shift keying (OAM-SK) and OAM division multiplexing (OAM-DM). For OAM-SK, the OAM states of the OV beams are regarded as a modulation format that enables the encoding of information by dynamic switching of spatial light modulators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The superior security advantages of OAM channels have also been demonstrated in both classical and quantum communication systems. [14][15][16][17][18][19] OAM-based optical communications can be classified into two different categories: OAM shift keying (OAM-SK) and OAM division multiplexing (OAM-DM). For OAM-SK, the OAM states of the OV beams are regarded as a modulation format that enables the encoding of information by dynamic switching of spatial light modulators.…”
Section: Introductionmentioning
confidence: 99%
“…For OAM-SK, the OAM states of the OV beams are regarded as a modulation format that enables the encoding of information by dynamic switching of spatial light modulators. 7,[19][20][21][22] For OAM-DM, the OAM states are considered to be fixed channels to be used to carry information with the advantages of high bit rates and low bit error rates (BERs). 13,23 In a state-of-the-art demonstration of an OAM-based FSO communication system, 2.56 Tbit s 21 data transmission was obtained by the multiplexing of four OAM beams with two polarization states.…”
Section: Introductionmentioning
confidence: 99%
“…Allen et al (1992) showed that a HermiteGaussian laser beam (zero OAM) can be transformed into a Laguerre-Gaussian beam (non-zero OAM) using a pair of cylindrical lenses. Subsequently, several other methods have been developed to generate POAM in the laboratory (Oemrawsingh et al 2004;Gibson et al 2004;Gruneisen et al 2008). LaguerreGaussian beams are known as optical vortex beams because of their phase structure which is proportional to e ımφ , using the azimuthal angle, φ, and the OAM index, m. All of the photons in these optical vortex beams carry m of OAM (Harwit 2003).…”
Section: Introductionmentioning
confidence: 99%
“…LaguerreGaussian beams are known as optical vortex beams because of their phase structure which is proportional to e ımφ , using the azimuthal angle, φ, and the OAM index, m. All of the photons in these optical vortex beams carry m of OAM (Harwit 2003). Identifying the states from such beams however, can be problematic and several different types of OAM sorters have been developed (Gruneisen et al 2008;Lavery et al 2011a,b;Sponselli & Lavery 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial light modulators (SLMs) have been utilized to generate OAM states and superpositions of OAM states using modulo 2π phase control [9,10] and computergenerated holography [12] to achieve both amplitude and phase modulation. Thin holograms in conjunction with single-mode optical fibers have been used to detect OAM states, but do not provide a means of separating OAM states with high efficiency [7,8,10,11].…”
Section: Introductionmentioning
confidence: 99%